2003
DOI: 10.1007/s00125-003-1170-0
|View full text |Cite
|
Sign up to set email alerts
|

PAI-1 polymorphisms modulate phenotypes associated with the metabolic syndrome in obese and diabetic Caucasian population

Abstract: Aim/hypothesis. Plasminogen activator inhibitor-1 (PAI-1) is a main regulator of the endogenous fibrinolytic system and modulates the thrombosis progression. We analyzed genetic contributions of PAI-1 mutations to the metabolic syndrome and to its complications. Methods. PAI-1 promoter and coding sequences were screened for mutations. Genotypes were determined for 1067 unrelated individuals of a French Caucasian cohort, selected for diabetes and obesity. Association between PAI-1 polymorphisms and phenotypes r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
6

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 46 publications
1
39
0
6
Order By: Relevance
“…Lopes et al (84) analyzed genetic contributions of PAI-1 mutations to the diabetes and to its complications for over 1,000 unrelated individuals of a French Caucasian cohort, selected for diabetes and obesity. They were looking for an association between PAI-1 polymorphisms and phenotypes related to diabetes.…”
Section: Diabetic Vascular Disease and Pai-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Lopes et al (84) analyzed genetic contributions of PAI-1 mutations to the diabetes and to its complications for over 1,000 unrelated individuals of a French Caucasian cohort, selected for diabetes and obesity. They were looking for an association between PAI-1 polymorphisms and phenotypes related to diabetes.…”
Section: Diabetic Vascular Disease and Pai-1mentioning
confidence: 99%
“…The authors found five SNP variants of which two promoter polymorphisms were associated with higher fasting glucose concentrations (P=0.006 and P=0.0004, for -765 4G/5G and -844 A>G, respectively) and insulin (P=0.05 and P=0.008, for -765 4G/5G and -844 A>G, respectively) (84). They suggest that PAI-1 polymorphisms probably induce a more severe insulin-resistant metabolic profile in diabetes, and further increase the risk for coronary heart disease in diabetic patients (84).…”
Section: Diabetic Vascular Disease and Pai-1mentioning
confidence: 99%
“…One way to verify this hypothesis is to look for a relation between single nucleotide polymorphisms (SNPs) influencing PAI-1 expression or activity, MI, and parameters belonging to the MetS. Several SERPINE1 (formerly PAI-1) gene SNPs have been identified, [21][22][23] among which the polymorphism 4G/5G (rs1799889) located in position Ϫ675 of the promoter region has been quite extensively studied. The 4G allele has been shown to be associated with increased SERPINE1 transcription compared with the 5G allele in in vitro studies 21,24 and with increased plasma PAI-1 levels in vivo.…”
mentioning
confidence: 99%
“…The promoter's two polymorphisms and the polymorphism Ala15Thr also showed association with CVD in diabetic persons (-765 4G/5G: 0.56/0.51, p=0.05; -844 A>G: 0.63/0.57, p=0.02; Ala15Thr: 0.91/0.88, p=0.04). In summary, these polymorphisms increase the risk of CVD in diabetic individuals (102).…”
Section: Decrease Of Fibrinolysismentioning
confidence: 97%